Profilin-1 over-expression upregulates PTEN and suppresses AKT activation in breast cancer cells - Das, Tuhin (2009)
Profilin-1 (Pfn1), a ubiquitously expressed actin-binding protein, has been regarded as a tumor-suppressor molecule for breast cancer. Since AKT signaling impacts cell survival and proliferation, in this study we investigated whether AKT activation in breast cancer cells is sensitive to perturbation of Pfn1 expression. We found that even a moderate overexpression of Pfn1 leads to a significant reduction in phosphorylation of AKT in MDA-MB-231 breast cancer cells. We further demonstrated that Pfn1 over-expression in MDA-MB-231 cells is associated with a significant reduction in the level of the phosphoinositide regulator of AKT, PIP(3), and impaired membrane translocation of AKT that is required for AKT activation, in response to EGF stimulation. Interestingly, Pfn1-overexpressing cells showed post-transcriptional upregulation of PTEN. Furthermore, when PTEN expression was silenced, AKT phosphorylation was rescued, suggesting PTEN upregulation is responsible for Pfn1-dependent attenuation of AKT activation in MDA-MB-231 cells. Pfn1 overexpression induced PTEN upregulation and reduced AKT activation were also reproducible features of BT474 breast cancer cells. These findings may provide mechanistic insights underlying at least some of the tumor-suppressive properties of Pfn1.